PENGARUH UNCONDITIONAL DAN CONDITIONAL CONSERVATISM TERHADAP FINANCIAL DISTRESS - Nanda Ismi Kumalawati; Rizka Indri Arfianti (Jurnal Bina Akuntansi, 2018)
Financial distress is increasingly faced by some companies early in bankruptcy; it’s usually caused by the improper basis of decision making and the unavailability of cash. Therefore, financial distress is very important to know as early as possible so it can be resolved and no bankruptcy happens. Conservatism is considered to be one factor that can reduce the risk of financial distress. So this study aims to examine the influence of conservatism on financial distress. The sample of the company used manufacturing companies during the period 2014-2016, this study also testing some companies that have experienced of financial distress during the period of observation. Data analysis techniques use multiple linear regression analysis. Through the results of this study, it can be concluded that unconditional conservatism and conditional conservatism proved to negatively affect financial distress.